A Survey on Artificial Intelligence in Biomedical Sciences - Dr. P. Bhargavi, K.V. Naga Deepthi (Mathematical Statistician and Engineering Applications, 2023)
The study of “intelligent machines” is Artificial Intelligence (AI), and it has applications in various sectors. Similar to how other general-purpose technologies and novel AI applications in workplace of the future raise significant issues for safety and health, it is predicted that AI will have a globally transformative impact on economic and social structures as more applications are integrated into daily life. With a particular emphasis on applications in health, medicine, pharmacology, toxicology, hematology, drug discovery, multi-omics, bioinformatics, nanotechnology and, biotechnology, this review aims to familiarize readers with the broad areas of AI. It also outlines the most recent developments in the field of AI research for medical applications. As new opportunities and concerns materialize, it is as crucial to recognize and comprehend these threats as it is to realize the AI approach itself. Therefore, mitigating the negative consequences of AI on human safety, health, and well-being will need a comprehension of both its potential and its challenges for the future work.